Smart farming in Thailand - Supalin Tiammee (2020)
© 2019 IEEE. Thailand's economic growth depends on agriculture. Roughly 30 to 40 percents of the total employment in Thailand is in the agricultural sector, but this group of people do not earn enough to spend on a daily basis. In this study, we proposed two production functions for Thai agriculture: with and without entrepreneurships. Entrepreneurship in agriculture is defined based on Schumpeter framework. In the first model, the Cobb- Douglas production function is applied to agricultural production without entrepreneurship and the stochastic frontier analysis is applied as an estimation technique to estimate the parameters. In the second model, the entrepreneurship variable is part of land, capital and labor inputs. Maximum likelihood estimation is used to find the estimated parameters. The results show that the returns to scale obtained from the developed production function with entrepreneurship are greater than those obtained from the production function without entrepreneurship.